Untersuchung diffus spiegelnder Oberflächen mittels Infrarotdeflektometrie - Höfer, Sebastian (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2017)
Thermal infrared deflectometry is based on the effect that rough surfaces, although having a dull appearance in the visual spectrum, exhibit a specular reflection in the thermal infrared spectrum and therefore enabling surface inspection with the method of deflectometry. This work covers the problems of generating the required thermal code patterns. The evaluation either adapts established methods from deflectometry, or new methods are introduced.